REGULAR FUNCTIONAL EXERCISES AND THEIR IMPACT ON DEVELOPING SOME PHYSICAL FITNESS COMPONENTS FOR INTERMEDIATE STUDENTS - Alaa Hadi Ali Kamar Al-Quraishi (Universitas Negeri Jakarta, 2025)
Objectives. This research was initiated due to the observed weakness among second-grade intermediate students in several basic components of physical fitness, particularly balance, flexibility, and muscular strength. This condition is largely attributed to a lack of structured physical activity and the absence of lessons incorporating suitable functional exercises. Therefore, the study aimed to (1) design a regular functional exercise program to enhance specific physical fitness components and (2) identify the impact of these exercises on the physical fitness development of second intermediate grade students. Materials and Methods. The research population consisted of 80 students, from which a sample of 50 was selected and divided equally into an experimental group (n=25) and a control group (n=25). The study ensured sample homogeneity and utilized various tools and measurement instruments, including appropriate physical tests. Functional exercises were implemented for the experimental group over a specified period, while the control group followed the standard curriculum. Data were analyzed using appropriate statistical methods to determine significant differences between pre- and post-test results. Results. The results revealed significant improvements in the experimental group compared to the control group across the targeted fitness components: motor balance, flexibility, and muscular strength. The implementation of functional exercises and motor games contributed to better muscular coordination, improved balance, and faster response times. These enhancements positively influenced the students' performance in daily physical activities. Conclusion. The study concluded that regular functional exercise programs are effective in improving key components of physical fitness among second-grade intermediate students. Functional training not only strengthens motor abilities but also enhances students’ engagement and physical performance in everyday sports and physical education contexts.